Administration of Ethanol Extract of Black Soybean Seeds (Glycine max (L.) Merr.) on the Number of Ovarian Tertiary Follicles and Serum Estradiol Levels in Wistar-Strain Rats (Rattus novergicus) Exposed to Cigarette Smoke - Widjaja, Danielle Karen; Ruma, I Made Winarsa; Widianti, I Gusti Ayu (Journal of Biomedicine and Translational Research, 2025)
Background: Premature ovarian insufficiency is ovarian aging that occurs before the age of 40, with a global prevalence of 1.1%. Premature ovarian insufficiency can be induced by environmental exposures, particularly through free radicals generated by cigarette smoke.Objective: The purpose of this study was to prove that the administration of ethanol extract of black soybean (Glycine max (L.) Merr.) can inhibit the decrease in ovarian tertiary follicle count and serum estradiol levels in Wistar strain rats (Rattus norvegicus) exposed to cigarette smoke.Methods: This research is an experimental study with a post-test-only control group design involving 30 Wistar-strain rats (Rattus norvegicus) that met the inclusion criteria. The rats were divided into five groups: group N (normal), group K (control), and group P1-P3 which received black soybean seed extract (Glycine max (L.) Merr.) at doses of 375 mg/kgBW (P1), 750 mg/kgBW (P2), and 1500 mg/kgBW (P3) administered orally via gavage every day for 28 days. The control group and treatment groups were exposed to cigarette smoke, after the administration of the extract, for 2 hours per day, 5 days a week, for 28 days. Serum estradiol levels (ng/L) were measured using the ELISA method, and ovarian tissue samples were collected for counting the number of ovarian tertiary follicles.Results: There was a significant difference in serum estradiol levels (p < 0,001), with the highest serum estradiol level observed in Group P1 (564.4 ± 74.28) and the lowest in Group K (116,7 ± 38,01).  There was no significant difference in the number of ovarian tertiary follicles (p=0,645).Conclusion: The ethanol extract of black soybean seeds (Glycine max (L.) Merr.) at a dose of 375 mg/kg BW significantly inhibits the decrease in estradiol levels but did not affect the number of ovarian tertiary follicles in Wistar strain rats (Rattus norvegicus) exposed to cigarette smoke.